Wcześniak w POZ – postępowanie profilaktyczno-lecznicze i zalecenia dotyczące realizacji programu szczepień ochronnych - Roemer-Ślimak, Roma; Ligucka, Monika; Mastalerz-Migas, Agnieszka (Lekarz POZ, 2016)
In the case of premature babies, especially those born before the end of the 28th week of pregnancy, morbidity and mortality rates are high, and damage to the nervous system and psychomotor development disorders are not uncommon. In approx. 20% of premature births it is impossible to determine the cause. The most common complications of prematurity refers to the respiratory, circulatory and digestive systems. Family doctors should be aware of those complications while taking care of prematurely born children. For a family doctor premature babies are those groups of patients who require the most attention and rapid response in the event of capture abnormalities. When taking care it is important to coordinate actions with a group of specialists who help and control the growth of prematures.